Electrochemical Behavior of AA5005 Aluminum Alloy in Acidic Chloride-Based Medium Containing CeO2 Nanoparticles. Issue 14 (18th October 2018) - Ecco, L. G.; Rossi, S.; Deflorian, F.; Fedel, M.
Abstract : The electrochemical response of bare aluminum AA5005 alloy immersed in acidified aqueous 0.1 M NaCl (pH≈3, aerated) with and without cerium oxide nanoparticles was studied via polarization curves and electrochemical impedance spectroscopy (EIS). The stability of the ceria particles in acidified aqueous medium was studied by means of transmission electron microscopy (TEM) and zeta-potential surface analysis. Both anodic and cathodic polarization curves of AA5005 electrode immersed in the electrolytes containing nanoceria showed lower corrosion rates with respect to the aluminum immersed in the same electrolyte without nanoceria. EIS investigations revealed an increase in the impedance at low-frequency range for the AA5005 panels immersed in the ceria-containing electrolytes wherein the Al electrodes switched from resistive to a more capacitive their electrochemical response after certain time of immersion. SEM images confirmed the responses from the electrochemical tests. No evident proof of corrosion attack was detected at the surface of Al electrodes after 200 h of immersion in the acidified chloride based electrolytes containing cerium oxide nanoparticles.